Scattered trees in an oil palm landscape: Density, size and distribution - Yevgeniya Korol; Watit Khokthong; Zemp, Clara; Bambang Irawan; Holger Kreft; Dirk Hölscher (My University, 2021)
In tropical landscapes dominated by oil palm monocultures, scattered trees can contribute to biodiversity, regulate diverse ecosystem functions and deliver goods and services. However, basic quantitative information about such trees is often lacking. The objectives of our study were to identify the landscape-wide density and distribution patterns of scattered trees in an oil-palm-dominated area of Sumatra (Indonesia), and to estimate their size. The study area with the total of 1120 ha was situated in Jambi province in the lowlands of Sumatra. In 2016, the year of our assessment, 83% of the area was covered by oil palm monocultures including industrial and smallholder plantations; other land-use types included rubber plantations and secondary forests. An earlier land-use classification suggests that oil palm cultivation began before 1990 on 41% of the area. The study area was mapped in 2016 using a fixed-wing drone equipped with red-green-blue and near-infrared cameras. We counted all visible trees in the aerial image. In the entire study region, we detected 10.1 scattered trees/ha. In areas where oil palm plantations were established before 1990, the tree density was 67% lower than in the area where oil palm was introduced later. The median tree crown diameter was 4.5 m, which corresponds to an estimated diameter at breast height of 12 cm; thus, most trees were small-statured. The trees were spatially clustered and often aligned along roads and rivers. In conclusion, we found a considerable number of scattered, mostly small-statured trees. This suggests that most trees were young and disappeared before reaching larger dimensions. To ensure the survival of trees and further provision of related ecosystem services, scattered trees in the oil palm landscape need to be conserved and/or restored.
Keywords: Drone; Human-modified landscape; Land-use history; Tree size; Trees outside forest; UAV